Tính giá trị của biểu thức:
a) 3 + 4 + 5 – 7;
b) 2. 3. 4. 5: 6
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a)
\(\begin{array}{l}A = \left( {2 + \frac{1}{3} - \frac{2}{5}} \right) - \left( {7 - \frac{3}{5} - \frac{4}{3}} \right) - \left( {\frac{1}{5} + \frac{5}{3} - 4} \right).\\A = \left( {\frac{{30}}{{15}} + \frac{5}{{15}} - \frac{6}{{15}}} \right) - \left( {\frac{{105}}{{15}} - \frac{9}{{15}} - \frac{{20}}{{15}}} \right) - \left( {\frac{3}{{15}} + \frac{{25}}{{15}} - \frac{{60}}{{15}}} \right)\\A = \frac{{29}}{{15}} - \frac{{76}}{{15}} - \left( {\frac{{ - 32}}{{15}}} \right)\\A = \frac{{29}}{{15}} - \frac{{76}}{{15}} + \frac{{32}}{{15}}\\A = \frac{{ - 15}}{{15}}\\A = - 1\end{array}\)
b)
\(\begin{array}{l}A = \left( {2 + \frac{1}{3} - \frac{2}{5}} \right) - \left( {7 - \frac{3}{5} - \frac{4}{3}} \right) - \left( {\frac{1}{5} + \frac{5}{3} - 4} \right)\\A = 2 + \frac{1}{3} - \frac{2}{5} - 7 + \frac{3}{5} + \frac{4}{3} - \frac{1}{5} - \frac{5}{3} + 4\\A = \left( {2 - 7 + 4} \right) + \left( {\frac{1}{3} + \frac{4}{3} - \frac{5}{3}} \right) + \left( { - \frac{2}{5} + \frac{3}{5} - \frac{1}{5}} \right)\\A = - 1 + 0 + 0 = - 1\end{array}\)
\(a)\left(-\dfrac{3}{4}\div\dfrac{2}{-3}\right)\times\dfrac{-5}{7}\)
\(=\dfrac{9}{8}\times\dfrac{-5}{7}\)
\(=\dfrac{-45}{56}\)
\(b)\dfrac{-2}{-5}\div\left(\dfrac{7}{-5}\div\dfrac{-3}{2}\right)\)
\(=\dfrac{2}{5}\div\left(\dfrac{7}{-5}\div\dfrac{-3}{2}\right)\)
\(=\dfrac{2}{5}\div\dfrac{14}{15}\)
\(=\dfrac{3}{7}\)
a) (2/5 x 25/29) + (3/5 x 25/29)
= (50/145) + (75/145)
= 125/145
b) (5/2 x 3/7) - (3/14 : 6/7)
= 15/14 - (3/14 x 7/6)
= 15/14 - 1/2
= (30/28) - (14/28)
= 16/28
= 4/7
c) (15/4 : 5/12) - (6/5 : 11/15)
= (15/4 x 12/5) - (6/5 x 15/11)
= 180/20 - 90/55
= 9 - 18/11
= (99/11) - (18/11)
= 81/11
= 7 4/11
a) (2/3) + (20/21 x 3/2 x 7/5)
= 2/3 + (60/210)
= 2/3 + 2/7
= (14/21) + (6/21)
= 20/21
b) (5/17 x 21/32 x 47/24 x 0)
= 0
c) (11/3 x 26/7) - (26/7 x 8/3)
= (286/21) - (208/21)
= 78/21
= 3 9/21
= 3 3/7
a) (25/8) : x = 5/16
=> (25/8) x (16/5) = x
=> 4 = x
b) x + (7/15) = 6/15
=> x = (6/15) - (7/15)
=> x = -1/15
c) x : (28/49) = 7/12
=> x x (49/28) = 7/12
=> x = (7/12) x (28/49)
=> x = 1/2
a) 6 x x = (5/8) : (3/4)
=> 6x = (5/8) x (4/3)
=> 6x = 20/24
=> 6x = 5/6
=> x = (5/6) / 6
=> x = 5/36
câu,b,không,đủ,thông,tin,nhan,bạn.
A)\(\dfrac{7}{20}-\left(\dfrac{5}{8}-\dfrac{2}{5}\right)\)
\(=\dfrac{7}{20}-\left(\dfrac{25}{40}-\dfrac{16}{40}\right)\)
\(=\dfrac{7}{20}-\dfrac{9}{40}\)
\(=\dfrac{14}{40}-\dfrac{9}{40}=\dfrac{5}{40}=\dfrac{1}{8}\)
B) \(\dfrac{5}{6}+\left(\dfrac{5}{9}-\dfrac{1}{4}\right)\)
\(=\dfrac{5}{6}+\left(\dfrac{20}{36}-\dfrac{9}{36}\right)\)
\(=\dfrac{5}{6}+\dfrac{11}{36}\).
\(=\dfrac{30}{36}+\dfrac{11}{36}=\dfrac{41}{36}\)
C) \(\dfrac{9}{10}-\left(\dfrac{2}{5}-\dfrac{3}{10}\right)+\dfrac{7}{20}\)
\(=\dfrac{9}{10}-\left(\dfrac{4}{10}-\dfrac{3}{10}\right)+\dfrac{7}{20}\)
\(=\dfrac{9}{10}-\dfrac{1}{10}+\dfrac{7}{20}\)
\(=\dfrac{18}{20}-\dfrac{2}{20}+\dfrac{7}{20}=\dfrac{23}{20}\)
a: =7/20-5/8+2/5
=14/40-25/40+16/40
=5/40=1/8
b: =5/6+5/9-1/4
=30/36+20/36-9/36
=41/36
c: =9/10-2/5+3/10+7/20
=12/10-2/5+7/20
=7/20+6/5-2/5
=7/20+4/5
=7/20+16/20
=23/20
a)\(\frac{3}{7}\times\frac{1}{3}+\frac{10}{7}=\frac{1}{7}+\frac{10}{7}=\frac{11}{7}\)
b)\(\frac{9}{5}-\left(\frac{27}{36}-\frac{4}{36}\right)=\frac{9}{5}-\frac{23}{36}=\frac{324}{180}-\frac{115}{180}=\frac{209}{180}\)
a)3/7: 3+5x2/7
=1/7+10/7
=11/7
b)9/5-(3/4-1/9)
=9/5-23/36
=209/180
10.213
11. 2 giờ 55 phút
12. 4 ngày 21 giờ
13.
a: 6,008
b: 4500
c: 5,628
d: 4,009
14.
a,8579 cm2
b,32,04 m2
c,187200m2
d,5,017 tấn
14:
a: \(85.79km^2=857900000000cm^2\)
b: \(32m^24dm^2=32.04m^2\)
c: \(1872dm^2=18.72m^2\)
d: 5 tấn 17kg=5,017 tấn
13:
a: \(6dm^38cm^3=6.008dm^3\)
b: \(4.5m^3=4500dm^3\)
c: \(5628dm^3=5.628m^3\)
d: \(4m^39dm^3=4.009m^3\)
12: =108h:3+80h
=36h+80h=116h
10:
3h18p+7h21p:3
=198p:441p:3
=198p+147p=345p
\(\frac{\frac{3}{5}+\frac{3}{7}-\frac{3}{11}}{\frac{4}{5}+\frac{4}{7}-\frac{4}{11}}=\frac{3\left(\frac{1}{5}+\frac{1}{7}-\frac{1}{11}\right)}{4\left(\frac{1}{5}+\frac{1}{7}-\frac{1}{11}\right)}\)\(=\frac{3}{4}\)
\(M=\frac{\frac{3}{5}+\frac{3}{7}-\frac{3}{11}}{\frac{4}{5}+\frac{4}{7}-\frac{4}{11}}\)
\(M=\frac{3.\left(\frac{1}{5}+\frac{1}{7}-\frac{1}{11}\right)}{4.\left(\frac{1}{5}+\frac{1}{7}-\frac{1}{11}\right)}\)
\(M=\frac{3}{4}\)
a: \(x:5=\dfrac{15}{14}\\ \Rightarrow x=\dfrac{15}{70}=\dfrac{3}{14}\)
a) 3 + 4 + 5 – 7 = 7 + 5 – 7 = (7 – 7) + 5 = 0 + 5 = 5
b) 2. 3. 4. 5: 6 = 6. 4. 5: 6 = 4. 5. (6: 6) = 20. 1 = 20
A, 3+4+5-7
=7-7+5
=0+5
=5
B,2.3.4.5:6
=6:6.4.5
=1.4.5
=4.5
=20